A Multidimensional Study of the Law of Goods and Services Procurement Contracts in Indonesia - Hartanto, Hartanto; Luthfan, Gusti Fadhil Fithrian; Syakdiah, Syakdiah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Government procurement of goods/services always changes in the context of presidential regulations (Perpres), by making these regulations complete and in more detail; In this case, it is certainly a positive development to provide legal protection for contracting parties in the form of goods/services procurement agreements. Agreement or akad (Arabic) which is interpreted as a bond or conclusion; Meanwhile, according to the term, a contract is a mutual agreement or commitment, whether verbal, signed or written, between two/more parties which has binding legal consequences to carry it out. This research analyzes the principle of freedom of contract and balance, which is a principle that is generally used as a reference, even though it seems that there has been a violation of this principle, legally the contract is still acceptable; On the legal side, there is a backbone in the field of civil law, but in its development it often overlaps with the field of criminal law (corruption), and in this research it is linked to Islamic law. The perspective of Islamic law has stated that in the context of civil law a broken promise is qualified as a group that betrays Allah SWT; Meanwhile, according to criminal law, corruption is contrary to the theory of benefit.